Optimal replication of random vectors by ordinary integrals - Dokuchaev, Nikolai (Elsevier BV, North-Holland, 2013)
We consider a problem of replication of random vectors by ordinary integrals in the setting when an underlying random variable is generated by a Wiener process. The goal is to find an optimal adapted process such that its cumulative integral at a fixed terminal time matches this variable. The optimal process has to be minimal in an integral norm.